STRATEGI PENGEMBANGAN POTENSI DESA WISATA SIDAN, KABUPATEN GIANYAR, BALI - Putu Arina Hermarani; Karlina Mechtildis Sindu; I Putu Gede Sukaatmadja; Ni Nyoman Kerti Yasa (Jurnal Pijar, 2023)
Sidan Village is a village located in the eastern region of Gianyar Regency which is also known as a cultural heritage village. Sidan Village has been inaugurated as a Tourism Village since 2019 through a Tourism Village Certificate given by the Gianyar Regency Government. This research sees a great opportunity if the tourism potentials can be optimally developed in the Sidan Tourism Village. This research is a type of qualitative descriptive research with a data collection method in the form of a questionnaire. SWOT analysis is used to identify external factors of opportunities and threats with internal strengths and weaknesses. The formulation of the Sidan Tourism Village development strategy uses an Internal-External (IE) matrix analysis. Based on the results of the analysis, Sidan Tourism Village is in quadrant I or in a growth and build position. This position shows that Sidan Tourism Village has an integrative or intensive strategy.